Glassy Metals - Russew, Krassimir; Stojanova, Liljana; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
The topics discussed in this book focus on fundamental problems concerning the structural relaxation of amorphous metallic alloys, above all the possibility of studying it on the basis of viscous flow behavior and its relation to rheological anomalies, such as bend stress relaxation, thermal expansion, specific heat, density changes, and crystallization. Most relaxation studies deal with the relaxation changes of a single definite material property, and not with a wider spectrum of physical properties integrated into a common framework. This book shows that it is possible to describe these property changes on the basis of a more comprehensive theoretical understanding of their mechanism.
1 Introduction -- 2. Most important methods for production of ribbon-like and bulk amorphous metallic alloys -- 3. Experimental methods for determination of the magnitude and temperature dependence of the viscosity of amorphous metallic alloys -- 4. Viscous behavior of amorphous ribbon-like metallic alloys depending on different factors -- 5. Basic concepts of the Free Volume Model. Structural relaxation and viscosity in the framework of the model -- 6.  Glass forming ability, crystallization and viscosity of rapidly solidified amorphous Cо100-xZrx and Cu100-xZrx alloys -- 7 Bend stress relaxation of amorphous metallic alloys under isothermal and non-isothermal heating conditions -- 8 Structural relaxation in various amorphous metallic alloys studied via direct viscosity and bend stress relaxation measurements -- 9. Thermal expansion and heat capacity of amorphous metallic alloys. Interpretation of their anomalous behavior in the framework of FVM -- 10 Relation between the density changes and the thermal expansion anomalies in the amorphous metallic alloys -- 11 Crystallization kinetics of bulk amorphous metallic alloys  and its relation to the forgoing relaxation processes -- 12 Mechanical properties of amorphous metallic alloys and their relation to the viscosity characteristic parameters -- 13 Properties and application of amorphous metallic alloys.
Keywords: Materials science; Materials Science